Sudden Sensorineural Hearing Loss (SSNHL): Case Report - Fikrilah Abdul Azis; Afiya Shafa Kamilah; Arifiana Larasati Restyani; Athaya Miraghassani; Henny Widyastuti (Rumah Sakit Unggul Karsa Medika, 2022)
Background Sudden sensorineural hearing loss (SSNHL) commonly known as sudden deafness, is an unexplained, rapid loss of hearing either all at once or over a few days in which patients experience a sudden drop in hearing. It is commonly linked to infections, head trauma, autoimmune diseases, iatrogenic, severe infections, blood circulation problems, neurological disorders, such as multiple sclerosis, disorders of the inner ear, such as Ménière’s disease, and even metabolic disorders such as diabetes mellitus. We presented a case of sudden sensorineural hearing loss in a secondary hospital in Indonesia to add more knowledge on this topic. Case presentation A 76-year-old male, had chief complain of a sudden right sided hearing loss. There were no other symptoms and he had no history of trauma to the ear. The patient had hypertension and consumed amlodipine and clonidine regularly. Patient had normal otoscopic and rhinoscopy examination results. Audiometry shown a hearing threshold of 37 dB in the left ear and 117 dB in the right ear, both in air and bone conducted pure-tone stimuli and tympanogram showed type As in both ears. A diagnosis of right ear sudden sensorineural hearing loss was made, and medical treatment consisted of methylprednisolone, acyclovir, mecobalamin, vitamin B6, ranitidine and omeprazole were given to the patient. Conclusion Pathophysiology of this disease are labyrinthine viral infection, labyrinthine vascular compromise, intracochlear membrane ruptures, and immune-mediated inner ear disease. In our case, we suspect that both ischemic vascular disease and viral infection as the cause of ISHHL. If there is no definitive or treatable etiology found, treatment regimen should be dictated by the most likely factors involved, which were systemic steroids and acyclovir in our case.